Water-Soluble Vitamins: Hypo- and Hypervitaminosis in Pediatric Population - Roberto Paparella; Fabiola Panvino; Lucia Leonardi; Ida Pucarelli; Michela Menghi; Ginevra Micangeli; Francesca Tarani; Marcello Niceta; Debora Rasio; Rouzha Pancheva; Marco Fiore; Luigi Tarani (Pharmaceutics)
Background/Objectives: Water-soluble vitamins, comprising the B-complex vitamins and vitamin C, are essential for normal growth, cellular metabolism, and immune function in pediatric populations. Due to limited storage in the body, these vitamins require consistent intake to prevent deficiencies. Pediatric populations, particularly infants and young children, face a heightened risk of both deficiency and, in rare cases, toxicity due to varying dietary intake and increased developmental needs. This review explores the clinical importance of water-soluble vitamins, focusing on hypo- and hypervitaminosis in children. Methods: A narrative review of the recent literature on the sources, recommended intakes, deficiency symptoms, and potential toxicities associated with each water-soluble vitamin was conducted. Results: Deficiencies in water-soluble vitamins can lead to diverse clinical outcomes, such as neurological, hematological, and immune-related symptoms, depending on the specific vitamin involved. Pediatric populations with increased nutritional needs, such as those experiencing rapid growth or with malabsorption conditions, are particularly vulnerable to vitamin insufficiencies. Conversely, although uncommon, excessive intake of certain water-soluble vitamins may cause mild toxicity, primarily gastrointestinal or neurological. Conclusions: Monitoring water-soluble vitamin levels and providing tailored nutritional support are critical to prevent the adverse effects of hypo- and hypervitaminosis in children. Further research is needed to refine pediatric nutritional guidelines and address the specific needs of young patients, supporting optimal health outcomes.